Dampak Tata Kelola Pemerintahan Terhadap Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia: Studi Kasus Negara Berkembang OKI - Yuliasti Linawati; Herlina Suzantia; Muhammad Ghafur Wibowo (TEMALI : Jurnal Pembangunan Sosial, 2021)
This study aims to determine the relationship between good governance on economic growth and the human development index in OIC developing countries. This study uses a panel data regression approach with the best model, the random effect model (REM). The research period used is from 2005 to 2018. The results show that voice and accountability, political stability, regulatory quality, and the rule of law significantly affect economic growth. In contrast, only the rule of law variable substantially impacts the human development index model. This research also highlights the importance of the government in improving good governance to promote higher economic growth and human development.